The effectiveness of project-based learning supported by digital media and local wisdom in social studies: impacts on student creativity and critical thinking - Luh Eka Puspa Aryani; I Putu Sriartha; Sukadi Sukadi (Indonesian Counselor Association (IKI), 2025)
This study was conducted in response to the limited use of innovative learning models, low student creativity, and insufficient critical thinking skills in Social Studies learning at SMP Negeri 7 Singaraja. The research aimed to analyze the implementation and effectiveness of a Project Based Learning model supported by Canva and integrated with local wisdom in improving students’ creativity and critical thinking skills. A quasi-experimental design with a nonequivalent control group was employed, involving an experimental class and a control class. Data were collected through observation, pretests, and posttests, and analyzed using statistical tests. The findings indicate that the implementation of the model was highly effective and significantly improved students’ creativity and critical thinking compared to conventional learning. These results highlight the potential of contextual, technology-supported project-based learning to transform Social Studies classrooms into spaces that foster meaningful and higher-order thinking.